Meninjau Kembali Sejarah Banten: Studi Kasus Pemerintahan Sultan Ageng Tirtayasa dan Implementasi Kepemimpinannya - Usman Manor (Salus Cultura: Jurnal Pembangunan Manusia dan Kebudayaan, 2021)
In 2020, the poor population in Banten Province reached 857,640 people or an increase compared to the previous year of 654,460 people. Whereas Banten has the potential for agriculture, animal husbandry, fisheries, mining, energy, and tourism which are actually capable of reducing poverty and optimizing people's welfare. In the past, Banten was a major port that experienced a heyday during the reign of Sultan Ageng Tirtayasa in 1651 to 1682. The implementation of the strategy used by Sultan Ageng Tirtayasa in bringing Banten glory needs to be studied so that a review of the history of Banten during the reign of Sultan Ageng is needed. Tirtayasa. Writing this journal aims to identify the problems experienced by Banten with reference to the reign of Sultan Ageng Tirtayasa who implemented the Defense Agency strategy. The method in writing this journal is a qualitative method which is strengthened by historical methods in the form of heuristics, criticism, interpretation, and historiography by collecting data through interviews and literature studies. The findings in this study are the ability of Sultan Ageng Tirtayasa to understand the context, make decisions by considering risks, and execute decisions in difficult circumstances known as the Defense Agency, making Banten survive in the face of the VOC economic blockade. The conclusion of writing this journal is that Banten is growing rapidly under the leadership of Sultan Ageng Tirtayasa as a large kingdom and international port. Despite facing an economic blockade by the VOC and political conflicts, the Defense Agency strategy implemented by Sultan Ageng Tirtayasa was actually able to make Banten experience a heyday. The implementation of the Defense Agency implemented by Sultan Ageng Tirtayasa can be applied today in order to revive the glory of Banten after the Covid-19 Pandemic.